Identification of Pigments and Obtaining of a Quantitative Model for the Attribution of Artistic Paintings by Portable X-Ray Fluorescence. Studio of Paintings of Servando Cabrera - Mendoza, A.; Maqueira, I.; Fernández, A. (Revista Cubana de Física; Vol 28 No 1E (2011): XII Symposium and X Congress of the Cuban Physical Society, 2011)
The colors palette´s pigments of artistic paintings are examined through a non destructive and in situ analysis with a portable X rays system based on a Si-PIN detector and a miniaturized X ray tube (50 kV, 1 mA). A method that allows to obtain a quantitative model for the attribution of paintings starting from the multivariate analysis of ¨target spectrum¨ data of unquestionable attributed paintings is propoused. The target spectrum of a painting was dened, for this development, as the average in all the measured points of the spectrum ranges that exclude the elements identier of pigment for each color. The pigments of the colors palette of the oustanding Cuban painter Servando Cabrera were identied. The classication model of the "target spectrum" predicted correctly two set of paintings selected among the paintings of Servando. The identication of pigments and the obtained attribution model contributed to a criterium about pigments and technique for the atribution of an an anonymous painting to the academic period of Servando.